Abdominal Adiposity Distribution in Diabetic/Prediabetic and Nondiabetic Populations: A Meta-Analysis - Jane J. Lee; S. Natasha Beretvas; Jeanne H. Freeland-Graves (Journal of Obesity)
Excess fat in the abdomen can be classified generally as visceral and subcutaneous adiposity. Evidence suggests that visceral adiposity has greater implications for diabetes than other fat depots. The purpose of this study is to explore the disparities in the distribution of abdominal adiposity in diabetic/prediabetic and nondiabetic populations and to identify moderators that influence the pattern of central obesity via a meta-analysis technique. The Hedges’ g was used as a measure of effect size and 95% confidence interval was computed. A total of 41 relevant studies with 101 effect sizes were retrieved. Pooled effect sizes for visceral and subcutaneous adiposity were 0.69 and 0.42, respectively. Diabetic/prediabetic populations exhibited greater visceral and subcutaneous adiposity compared to nondiabetic populations (Z=10.35, P<0.05). Significant moderator effects of gender (Z=-2.90) and assessment method of abdominal adiposity (Z=-2.17) were found for visceral fat (P<0.05), but not for subcutaneous fat. Type of health condition influenced both visceral (Z=-5.10) and subcutaneous (Z=-7.09) abdominal adiposity volumes (P<0.05). Abdominal adiposity distributions were significantly altered in the diabetic/prediabetic population compared to the nondiabetic population. Gender, assessment method of abdominal adiposity, and type of health conditions (diabetic/prediabetics) were identified as crucial moderators that influence the degree of abdominal adiposity.